Verrucous carcinoma in association with oral submucous fibrosis - C Pravda; H Srinivasan; D Koteeswaran; L Arathy Manohar (Wolters Kluwer Medknow Publications, 2011)
Oral verrucous carcinoma is a form of well differentiated squamous cell carcinoma characterized by exophytic over growth. It is slow growing and locally invasive tumor occurring in 6 th and 7 th decade of life. Smoking and chewing tobacco is found to be the most common etiological factor of verrucous carcinoma although oral leukoplakia may act as a predisposing factor. This is a rare case of oral varrucous Carcinoma seen in association with oral submucous fibrosis in a younger patient with long standing history of chewing tobacco.